SUPPORT A TOTAL AIRLINE SMOKING BAN. SMOKELESS FLYING (Tufts Archival Research Center, 2007)
Letter to members of the House of Representatives urging them to support legislation which would ban smoking on all flights. Cites toxicity of secondhand smoke as the reason behind the need for the ban. Points to the success of the trial ban and the ban on Canada's airlines as evidence of the feasibility of the legislation. Contains signatures from the senators supporting the bill.